Phytochemical screening of flavonoids with their antioxidant activities from rapeseed (Brassica napus L.). (September 2015) - Jing, Wen Guang; Fu, Jiang; Guo, Yan; Liu, An
Graphical abstract: Highlights: Phytochemical screening of flavonoids from rapeseed was reported. Three new flavonoid glycosides were isolated from the rapeseed. Protective antioxidant effect on ECV-30 cells was investigated. Most compounds had antioxidant effect with a concentration-dependent manner. The relationship of biological activity and structures was described. Abstract: Ten flavone compounds, including three new flavonoid glycosides, were isolated from defatted rapeseed, and their protective antioxidant effect on H2 O2 -induced oxidative damage in human umbilical vein endothelial cells (ECV-304) was investigated. Three new flavonoid glycosides were identified as kaempferol-3- O -[(6- O -sinapoyl)-β-d -glucopyranosyl-(1 → 2)-β-d -glucopyranoside]-7- O -β-d -glucopyranoside (8 ), kaempferol-3, 7-di- O -β-d -glucopyranoside-4'-O-(6-O-sinapoyl)-β-d -glucopyranoside (9 ), and kaempferol-3- O -[(3- O -sinapoyl)-β-d -glucopyranosyl-(1 → 2)-β-d -glucopyranoside]-7- O -β-d -glucopyranoside (10 ). The protective effects of all of the isolated compounds on H2 O2 -induced oxidative damage were assessed, and the activities of superoxide dismutase (SOD) and lactate dehydrogenase (LDH) were measured. All of compounds had a protective effect on H2 O2 -induced oxidative damage in ECV-304 cells and the presence of a substituted sinapoyl group and its position in the structures were used to elucidate the activity differences.